Collaborative innovation and activation in urban labour markets. (July 2021) - Lindsay, Colin; Pearson, Sarah; Batty, Elaine; Cullen, Anne Marie; Eadson, Will
Policymakers in the UK, having long supported centralised and marketised models of governance and delivery in the field of labour market activation, have recently begun to acknowledge the benefits of more localised, collaborative approaches to organising public services. Evidence from other European welfare states suggests that the case in favour of localised innovation may be particularly compelling in urban labour markets, where there can be pockets of severe disadvantage, but also networks of community stakeholders better able to support collaboration and innovation through user engagement. Drawing on the conceptual and empirical literature on 'collaborative innovation', this article discusses an example of good practice in innovative localised activation in city labour markets ('Making It Work' services targeting unemployed single parents in Scotland's two largest cities). Our analysis is based on 92 in-depth interviews with single parents and key stakeholders involved in service design and delivery. We identify benefits associated with multi-stakeholder collaborative governance, distributive leadership in programme management, and practices promoting the co-production of innovative services with single parents at the frontline. However, we also note tensions between localised services committed to innovation and empowerment, and an increasingly less interventionist but more punitive liberal welfare state. We conclude by identifying potential lessons for the governance, management and delivery of activation services in urban areas.